2016
DOI: 10.1002/ece3.2212
|View full text |Cite
|
Sign up to set email alerts
|

Cyto‐nuclear discordance suggests complex evolutionary history in the cave‐dwelling salamander, Eurycea lucifuga

Abstract: Our understanding of the evolutionary history and ecology of cave‐associated species has been driven historically by studies of morphologically adapted cave‐restricted species. Our understanding of the evolutionary history and ecology of nonrestricted cave species, troglophiles, is limited to a few studies, which present differing accounts of troglophiles’ relationship with the cave habitat, and its impact on population dynamics. Here, we used phylogenetics, demographic statistics, and population genetic metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(163 reference statements)
0
5
0
Order By: Relevance
“…In contrast, the analyses based on microsatellite data revealed two genetic groups with admixed populations and only 16.5% of the nuclear variance occurred among groups, which is indicative of high levels of mitochondrial genetic structure in the absence of significant nuclear structure in S. japonica . Such “mito‐nuclear” discordance is common in secondary contact zones (Bonnet, Leblois, Rousset, & Crochet, ; Edgington, Ingram, & Taylor, ; Fontenot, Makowsky, & Chippindale, ; Toews & Brelsford, ). We suspect that this phenomenon could be caused by the different introgression degrees observed for the mitochondrial and nuclear markers (e.g., Neiva, Pearson, Valero, & Serrão, ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the analyses based on microsatellite data revealed two genetic groups with admixed populations and only 16.5% of the nuclear variance occurred among groups, which is indicative of high levels of mitochondrial genetic structure in the absence of significant nuclear structure in S. japonica . Such “mito‐nuclear” discordance is common in secondary contact zones (Bonnet, Leblois, Rousset, & Crochet, ; Edgington, Ingram, & Taylor, ; Fontenot, Makowsky, & Chippindale, ; Toews & Brelsford, ). We suspect that this phenomenon could be caused by the different introgression degrees observed for the mitochondrial and nuclear markers (e.g., Neiva, Pearson, Valero, & Serrão, ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the phylogeographic break may reflect ancient allopatry succeeded by secondary contact and lineage merger, in which the microsatellite cline is far wider than our sampling and so not detectable. Some studies have posited that mtDNA can reflect historical processes, such as divergence in multiple refugia or past introgression, whereas nuclear markers more closely track the current demographic dynamics (Jockusch and Wake, 2002;Weisrock et al, 2005;Edgington et al, 2016). Further, by not selecting loci a priori with known clade-specific alleles (e.g., Alexandrino et al, 2005;Kuchta, 2007), we may not have been able to recover a subtle nuclear cline within our transect, although INTROGRESS suggests that none of our 10 loci are consistent with a cline or secondary contact.…”
Section: Discussionmentioning
confidence: 81%
“…The potential drawbacks of phylogeographic inference from mtDNA alone are well known (Flanders et al 2009), but in combination with nuclear markers, the data can provide valuable understanding of a species' evolutionary trajectory (Lefebvre et al 2016;Mende et al 2016). In particular, it has been suggested that mitochondrial loci might reflect a more ancient evolutionary history (Edgington et al 2016).…”
Section: Introductionmentioning
confidence: 99%